Zidovudine Pharmacokinetics in Premature Infants Exposed to Human Immunodeficiency Virus - Mirochnick, Mark (American Society for Microbiology, 1998)
We used population analysis techniques to determine zidovudine (ZDV) pharmacokinetic parameters in 15 preterm neonates (mean gestational age, 29.4 weeks; mean birth weight, 1,230 g) at a mean age of 5.5 days. The values of the pharmacokinetic parameters were as follows: clearance, 2.53 ± 0.44 ml/min/kg; volume of distribution, 1.59 ± 0.51 liters/kg; and half-life, 7.2 ± 1.5 h. For seven infants studied a second time, at a mean age of 17.7 days, an increase in the mean clearance (2.33 versus 4.35 ml/min/kg; P = 0.024) and a decrease in the half-life (7.3 versus 4.4 h; P = 0.003) were found. The ZDV clearance is low and the half-life is prolonged in premature neonates, but the clearance increases and the half-life decreases with postnatal age. Potentially toxic concentrations may accumulate in serum if the standard dosage for full-term infants is used. We suggest that initial ZDV dosing should be reduced to 1.5 mg every 12 h for preterm neonates.